Last Decade of Unconventional Methodologies for the Synthesis of Substituted Benzofurans - Lucia Chiummiento; Rosarita D’Orsi; Maria Funicello; Paolo Lupattelli (Molecules, 2020)
This review describes the progress of the last decade on the synthesis of substituted benzofurans, which are useful scaffolds for the synthesis of numerous natural products and pharmaceuticals. In particular, new intramolecular and intermolecular C–C and/or C–O bond-forming processes, with transition-metal catalysis or metal-free are summarized. (1) Introduction. (2) Ring generation via intramolecular cyclization. (2.1) C7a–O bond formation: (route a). (2.2) O–C2 bond formation: (route b). (2.3) C2–C3 bond formation: (route c). (2.4) C3–C3a bond formation: (route d). (3) Ring generation via intermolecular cyclization. (3.1) C7a-O and C3–C3a bond formation (route a + d). (3.2) O–C2 and C2–C3 bond formation: (route b + c). (3.3) O–C2 and C3–C3a bond formation: (route b + d). (4) Benzannulation. (5) Conclusion.